2006
DOI: 10.1021/jo052212q
|View full text |Cite
|
Sign up to set email alerts
|

Short Stereoselective Synthesis of α-Substituted γ-Lactams

Abstract: A concise, stereoselective synthesis of α-substituted γ-lactams is reported. γ-Lactam scaffolds 2 and 3 possessing an Evans' chiral auxiliary and two types of N-substituents were successfully alkylated with different electrophiles to give α-substituted γ-lactams with reasonable diastereoselectivities. The use of a masked carboxymethyl function off the lactam nitrogen provided a convergent means to α-substituted γ-lactam dipeptide isosteres.γ-Lactams, with their ψ angle constrained, are important constituents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…γ-Lactams and related motifs are important components of various biologically active compounds, natural products, and pharmaceuticals, and therefore, several effective methodologies for preparing a wide variety of γ-lactams, including α-, β-, and γ-substituted ones, have been reported. The development of efficient C–H bond functionalization reactions that proceed under benign conditions is a major goal of current research in organic chemistry, and studies along these lines have borne impressive fruit. Synthetic protocols allowing the cleavage of C–H bonds adjacent to nitrogen atoms under oxidative conditions in the presence of catalysts have been reported . For instance, Kantam and co-workers found that CuO NPs catalyzed the formation of N -aryl-γ-amino-γ-lactams via the oxidative coupling of aromatic amines with 2-pyrrolidinone (Figure ).…”
Section: Catalytic Applications Of Cu Nps In Organic Transformationsmentioning
confidence: 99%
“…γ-Lactams and related motifs are important components of various biologically active compounds, natural products, and pharmaceuticals, and therefore, several effective methodologies for preparing a wide variety of γ-lactams, including α-, β-, and γ-substituted ones, have been reported. The development of efficient C–H bond functionalization reactions that proceed under benign conditions is a major goal of current research in organic chemistry, and studies along these lines have borne impressive fruit. Synthetic protocols allowing the cleavage of C–H bonds adjacent to nitrogen atoms under oxidative conditions in the presence of catalysts have been reported . For instance, Kantam and co-workers found that CuO NPs catalyzed the formation of N -aryl-γ-amino-γ-lactams via the oxidative coupling of aromatic amines with 2-pyrrolidinone (Figure ).…”
Section: Catalytic Applications Of Cu Nps In Organic Transformationsmentioning
confidence: 99%
“…The synthesis of (±)-7 was achieved in two steps using a modification of the reported procedure for a related bromolactam. 3 Starting from acylation of benzylamine 4 with acid chloride 5, 4 bromolactam 7 as a racemic mixture. Attempts to separate the enantiomers were successful using preparative chiral supercritical fluid chromatography (SFC); however, each enantiomer quickly racemized back to (±)-7 during evaporation, thus necessitating the use of the racemic material in this, our original approach, with resolution now to occur at a later stage in the synthesis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The initial approach for the preparation of fragment 2 targeted X = Br, and the synthesis of bromolactam (±)- 7 is shown in Scheme . The synthesis of (±)- 7 was achieved in two steps using a modification of the reported procedure for a related bromolactam . Starting from acylation of benzylamine 4 with acid chloride 5 , base-promoted cyclization then afforded bromolactam 7 as a racemic mixture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were reacted with N -[(silyl)methyl]-β-lactam carbanions, generated under optimized conditions, to furnish moderate to good yields of the corresponding desilylated and α‘-functionalized N -methyl-β-lactams 26 − 36 . Interestingly, the method was applicable to all the α,β-substitution and N -protection patterns studied, including monosilyl-β-lactams 14 and 17 , and some of the α- N -Boc-α‘-carboxy-β-lactams prepared (e.g., 34 − 36 ) could be considered as internally constrained peptidomimetics, ready for incorporation into peptide chains by standard peptide synthesis techniques 2 Functionalization of N -[(silyl)Methyl]-β-lactams with Carbon Dioxide and Related Electrophiles entryβ-lactamYR 1 R 2 R 3 baseelectrophile a productEyield (%) b 1 10 Xc H H Bn s BuLi (−78) CO 2 26 CO 2 H 58 2 10 Xc H H Bn s BuLi/TMEDA (−78) ClCO 2 Bn 19 77 3 10 Xc H H Bn s BuLi (−78) ClCO 2 Bn 27 CO 2 Bn 45 4 10 Xc H H Bn n BuLi/TMEDA (−100) PhNCO 28 CONHPh 63 5 11 Xc H H i Bn n BuLi/TMEDA (−100) CO 2 29 CO 2 H 90 6 11 Xc H H i Bn n BuLi/TMEDA (−100) Me 3 SiNCO 30 CN 60 7 11 Xc H H i Bn n BuLi/TMEDA (−100) Me 3 SiNCO c 31 CONH 2 80 8 12 Xc H Ph Bn n BuLi/TMEDA (−100) PhNCO 32 CONHPh 74 9 14 Xc i Bn H …”
Section: Resultsmentioning
confidence: 99%